Investigating the effectiveness of process genre-based approach to teaching technical writing in a higher learning institution - Nordin, Shahrina Md (2006)
I wish to dedicate this work to my beloved parents, Md. Nordin b. Md. Nor and Halimah bt. Hj. Jaafar, who have always been a constant source of inspiration to me in my pursuit of education to the highest levels. The dedication also goes to my beloved brothers and sisters: Nadiah, Fahariyah, Fadzli, Fauzi and Rabiatul Adawiyah. In completing this thesis I am greatly indebted to my supervisor Dr. Norhisham bt Mohamad, without whose knowledge and insight, I would not have been able to come this far. My highest appreciation goes to her for guiding me through every step of the way. My heartfelt thanks to my immediate superior, Encik Mohd Noor Rosli b. Baharom, and my fellow colleagues and friends in General Studies Programme, Universiti Teknologi PETRONAS, for the abundant assistance and support I received throughout my studies. I am especially thankful to Associate Professor Dr. Mohamed b. Haleb for his constant support and guidance throughout the duration of this research work. Most of all, I want to thank my dear husband, Mohd Zairee Shah b. Mohamed Shah, for his continuous support and encouragement. My thanks also go to my beloved daughter Hannan Balqis, for her patience and affection.